Targeting B7-H3 enhances the efficacy of neoantigen-based cancer vaccine in combination with radiotherapy - Tao-Wei Ke; Chia-Yi Chen; William Tzu-Liang Chen; Yuan-Yao Tsai; Shu-Fen Chiang; Chi-Hsien Huang; Yu-Sen Lin; Te-Hong Chen; Tsung-Wei Chen; Ji-An Liang; K. S. Clifford Chao; Kevin Chih-Yang Huang (npj Vaccines)
Abstract The clinical response to immune checkpoint blockade (ICB) is limited in the majority of patients with colorectal cancer. These immune checkpoint proteins may not only inhibit T-cell-mediated antitumor immunity but also attenuate antigen presentation, including mutation-associated neoantigens. Here, we found that tumor B7-H3 levels may limit the therapeutic response to chemoradiotherapy in patients with locally-advanced rectal cancer. Knockdown of tumor B7-H3 significantly increased antigen presentation to increase T cell infiltration and killing ability, including neoantigen-specific T-cell response. Blockade of B7-H3 significantly augmented neoantigen-specific T cells response and remarkably enhanced the therapeutic efficacy of neoantigen-based cancer vaccines combined with radiotherapy, decreasing the risk of distant tumors in vivo. Taken together, these results demonstrated that targeting B7-H3 significantly enhanced the therapeutic efficacy of neoantigen cancer vaccines as well as radiotherapy by increasing the extent of neoantigen-specific T cells, even for PD-1/PD-L1 blockade-resistant colorectal cancers.